2008
DOI: 10.1111/j.1748-1716.2008.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional evolution of gonadotropin‐releasing hormone in vertebrates

Abstract: The neuropeptide gonadotropin-releasing hormone (GnRH) has a central role in the neural control of vertebrate reproduction. This review describes an overview of what is currently known about GnRH in vertebrates in the context of its structural and functional evolution. A large body of evidence has demonstrated the existence of three paralogous genes for GnRH (GnRH1, GnRH2 and GnRH3) in the vertebrate lineage. They are most probably the products of whole-genome duplications that occurred early in vertebrate evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
179
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(185 citation statements)
references
References 152 publications
5
179
0
4
Order By: Relevance
“…At present, it is generally accepted that GnRH regulates synthesis and release of pituitary gonadotropin (GTH) (see King and Millar 1992;Sherwood et al 1993). It has been shown that two or three molecular forms of GnRH exist, even within the same species (Oka 1997;Okuzawa and Kobayashi 1999;Okubo and Nagahama 2008). In addition, GnRH can act as a neuromodulator and has also been implicated in reproductive behavior in many species including teleost fish such as dwarf gourami Colisa lalia (Yamamoto et al 1997) and goldfish Carassius auratus (Volkoff and Peter 1999).…”
Section: General Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, it is generally accepted that GnRH regulates synthesis and release of pituitary gonadotropin (GTH) (see King and Millar 1992;Sherwood et al 1993). It has been shown that two or three molecular forms of GnRH exist, even within the same species (Oka 1997;Okuzawa and Kobayashi 1999;Okubo and Nagahama 2008). In addition, GnRH can act as a neuromodulator and has also been implicated in reproductive behavior in many species including teleost fish such as dwarf gourami Colisa lalia (Yamamoto et al 1997) and goldfish Carassius auratus (Volkoff and Peter 1999).…”
Section: General Introductionmentioning
confidence: 99%
“…Since two or three molecular forms of GnRH exist, even within the same species (see Oka 1997;Okuzawa and Kobayashi 1999;Okubo and Nagahama 2008), it is quite important to identify GnRH forms in the brain to understand the reproductive biology of fish. The presence of two forms of GnRH, salmon GnRH (sGnRH) and chicken GnRH-II (cGnRH-II), in the teleost brain was first reported in goldfish by employing reversed phase high performance liquid chromatography (rpHPLC) in conjunction with radioimmunoassay (RIA) (Yu et al 1988).…”
Section: -1 Identification Of Gnrh Forms By Hplc and Ria In Masu Samentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the GnRH3 group, which is currently known only in teleost fish, contains GnRH forms that are expressed by neurons located in the ventral forebrain. GnRH3 has been demonstrated to exert neuromodulatory functions (Fernald and White, 1999;Okubo and Nagahama, 2008).…”
Section: Introductionmentioning
confidence: 99%